Evaluating intraoperative cytology with histopathology diagnosis and its importance in ovarian tumors (Journal of Pathology of Nepal, 2020)
Background: Touch/ imprint cytology has been utilized for intraoperative evaluations of tumors to complement frozen sections in order to reach diagnosis prior to histopathology diagnosis. The main aim of this study is to find role of touch imprint in determining histopathology diagnosis of ovarian neoplasm.Materials and Methods: All together one hundred three cases were evaluated using both touch/imprint and histopathology diagnosis. The histopathology diagnoses consisted of Benign (n=85), borderline (n=4), and malignant (n=12). Touch imprint cytology consists of Negative for malignancy (n=90), Positive for malignancy (n=11) and inadequate (n=2). Inadequate smear was excluded from the study.Results: Both touch / imprint cytology were able to diagnose benign and malignant ovarian neoplasm. Out of 103 cases, in cytology showed 89.1% patients were negative and 10.9% patients were positive. Histopathology shows 84.2% of benign ovarian neoplasm, 3.9% borderline neoplasm and 11.9% of malignant. Diagnostic accuracy of touch/ imprint was 99% with sensitivity 100% and specificity was 91.67%. Positive predictive value was 98.89% and negative predictive value was 100%.Conclusion: Touch/ imprint cytology examination is simple, rapid and useful test in evaluation of ovarian neoplasms. It plays very important role in preliminary intraoperative diagnosis of benign and malignant ovarian neoplasms.